Aplikasi Manajemen 3E dalam Pengembangan Profesionalitas Guru - Rahman, Bujang (Jurnal Aplikasi Manajemen, 2015)
Teachers'professional development programs have been considered not be able toovercome the issues of lack teachers'qualities and students'learning outcome (Evans et al.,2009). This article aims to explain how the application of 3E (Experience, Expectation andEvidence) management model contributes to enhance teachers'professionalism. 168 teachersin Lampung province were involved in this study in order to investigate the extent ofExperience, Expectation and Evidence have contribution to their professionalism. Based onthe results of the regression analysis, these three factors gave significant contribution totheir professionalism 20.2% (p <0.05). 3E's management model provides an alternativeroad map on how teachers'professional development program should be implemented. Furtherexperimental researches on the implementation 3E management have an impact on theeffectiveness of teachers'learning in the classroom in which leading to the improvement ofstudents'learning outcomes become open.